Obsessive-compulsive disorder and Tourette Syndrome: is there a relationship? - Rosário, Maria Conceição do; Miguel Filho, Eurípedes Constantino (São Paulo Medical Journal, 1997)
The authors describe the main characteristics of Obsessive-Compulsive Disorder, the fourth most frequent psychiatric disease, and Tourette Syndrome. Considered completely separate disorders, there is growing scientific evidence that there is a connection between them. The authors present clinical, genetic and neuroimaging data reinforcing this idea, and call attention to the importance of research in this area, as they believe that the definition of more homogenous subgroups will facilitate the identification of biological markers and predictors of treatment response.